A case of granulomatous tonsillitis leading to the diagnosis of Crohn’s disease - Takeuchi, Mio; Kobayashi, Sei; Hibi, Hiroyuki; Uruma, Syuhei; Kobayashi, Hitome; Amari, Yasunobu (Stomato-pharyngology, 2023)
Introduction: Granulomatous tonsillitis is a very rare disease in which granulomas form in tonsil tissue. Various diseases such as tuberculosis, sarcoidosis, and Crohn’s disease have been implicated as causes, but in many cases the cause is unknown. Crohn’s disease is an inflammatory bowel disease and requires early diagnosis and treatment. We report a case of granulomatous tonsillitis that was diagnosed as Crohn’s disease after tonsillectomy. Case: The patient was a 28-year-old woman who underwent tonsillectomy for habitual tonsillitis. Histopathological examination of the palatine tonsils revealed the formation of a non-caseating epithelioid cell granuloma. A thorough systemic examination was performed, but did not lead to a diagnosis of the causative disease. On postoperative day 45, the patient began to have fever, gastrointestinal symptoms, and stomatitis. A lower gastrointestinal endoscopy was performed on postoperative day 73. The ileal mucosa showed easily hemorrhagic mucositis with longitudinal ulceration. A mucosal biopsy resulted in a diagnosis of Crohn’s disease. Treatment was initiated promptly, and the patient has remained in remission to this day. Conclusion: The granulomatous tonsillitis in this case was considered to be an oral lesion preceding Crohn’s disease. In cases of granulomatous tonsillitis with epithelioid cell granuloma, the possibility that Crohn’s disease is the cause should be fully considered.